Immunotherapy against angiogenesis-associated targets: evidence and implications for the treatment of malignant glioma. Issue 5 (May 2008) - Everson, Richard G; Graner, Michael W; Gromeier, Matthias; Vredenburgh, James J; Desjardins, Annick; Reardon, David A; Friedman, Henry S; Friedman, Allan H; Bigner, Darell D; Sampson, John H
Angiogenesis, the growth of new blood vessels from previously existing vasculature, is a requirement for tumor growth and metastasis. The first US FDA-approved drugs targeting angiogenesis have shown potential in the treatment of malignant gliomas. Immunotherapy as a treatment modality lends itself well to specifically targeting angiogenesis in tumors and may represent a powerful tool in the treatment of malignant gliomas. This review focuses on developments in immunotherapy targeting angiogenesis and tumor-vascular-specific endothelial cells using a variety of immunotherapeutic strategies including monoclonal antibodies and conjugated immunotoxins, as well as cellular, peptide, DNA and dendritic cell vaccines.